LAHAN PERKEBUNAN CITEKO BOGOR SEBAGAI CAMPING GROUND DENGAN KONSEP EKOWISATA - Utami, Nadya Rechtta (Puslitabmas Batam Tourism Polytecnic, 2022)
The Citeko plantation area is located in the Cisarua sub-district, Bogor Regency, this plantation area is used as an alternative area for camping by visitors who cannot visit the Gayatri Camping Ground. In this paper the author intends to find the potential of the land to be used as an ecotourism object, the purpose of this paper is none other than to discuss the Citeko plantation land which is considered to have potential as a camping tourism object by carrying the concept of ecotourism so that the natural preservation around the plantation is maintained. This study uses descriptive analysis. Primary data in this study were obtained from interviews with informants and direct observations of researchers at the research site, while secondary data in this study were obtained from literature sources and library sources. The results of the discussion in this journal are that plantation land located in Citeko, Bogor Regency is considered to be able to be used as an ecotourism object because it still has original nature and the ecology in the area is still very well preserved, but there are several problems in the area, namely the absence of facilities. to accommodate waste from visitors, there is no guidance from the local government and competent parties (Stakeholders), the local community is not prepared to process objects and there are no clear rules for visitors when traveling in the area.